Report from the International Workshop on the Role of Public Administration in Public Policies’ Design & 15th Anniversary of the Central European Public Administration Review - Polonca Kovač; Tina Jukić (Central European Public Administration Review)
In April 2018, the Faculty of Administration of the University of Ljubljana organised a two-day international workshop on the role of public administration in public policies' design. The workshop consisted of four parts: three sessions and one round table. In the first session, discussion was about evaluating public administration and public governance. The second session focused on the identification of the key success factors for effective public policies in Slovenia. These sessions were initiated based on the research project “Development of the model for monitoring and evaluation of development programmes and projects in public sector”, known as the ATENA project. The project is co-funded by the Slovenian Research Agency for the period 2016–2019 (no. J5-7557) and led by prof. dr. Mirko Vintar (cf. Mencinger et al., 2017). The third session was motivated by the European research project EUPACK (European Public Administration Country Knowledge), focused on the analysis of public administration characteristics and performance in EU Member States (see Thijs, Hammerschmid & Palaric 2018). A special part of the workshop was devoted to the 15th anniversary of the Central European Public Administration Review. Here, a round table was conducted with the editors-in-chief of established public administration journals from the region, followed by an editors and reviewers recognition awards ceremony. The discussions were all very fruitful, also thanks to the participation of several internationally recognised scholars from the Netherlands, Croatia, Germany, Slovakia, the Czech Republic, Romania and Slovenia, as well as around twenty representatives of Slovenian ministries, other administrative authorities and non-governmental organisations. In a dynamic debate that comprehensively covered the evaluation in public policy cycle and the role of public administration and university therein, numerous issues were discussed. Below is a report on the main topics discussed in the workshop.